Estudo morfométrico comparativo do sulco do seio sigmóideo e do forame jugular - Silvio Pereira Ramos Junior (2012)
Several authors have described distinct surgical techniques to approach temporal bone and jugular foramen tumors, indicating landmarks to identify and preserve neural and vascular structures, such as the sigmoid sinus. Jugular foramen, with its internal and neighboring anatomical structures of vital importance, becomes a challenge for the neurosurgeon when surgical lesions arise in it. The objectives of this thesis were to compare right and left sides of the same skull concerning described benchmarks and define craniometric differences between them. We have performed measurements between right and left sides on a same skull using anatomic references, such as the point of transition of grooves from transverse/sigmoid sinus, digastric point, jugular foramen and the groove from sigmoid sinus comparing both sides. The following measurements were performed on 50 dry adult human skulls: width of the sigmoid sinus at the projection of sinodural angle and digastric point, distance from the sigmoid sinus to between sinodural angle and the digastric point, distance from the sigmoid sinus to between digastric point and jugular foramen, width of the jugular foramen. These measurements were performed using digital paquimeter and the identification of the correspondent of digastric point on the internal surface of the skull was reached by skull transillumination with LASER or compass. As results, we obtained measurements for the width of sigmoid sinus at the projection of sinodural angle to be largest on the right side in 78% of the cases, and at the projection of the digastric point in 72%. The width of the jugular foramen was also larger on the right side in 84% of the cases. The distance of the sigmoid sinus at the projection of sinodural angle to the projection of digastric point was larger on the right side in 64% of the cases, and the distance from the sigmoid sinus at the projection to the jugular foramen was larger on the right side in 70% of the cases.